Studi Literatur Hubungan Supervisi dan Evaluasi Pendidikan dalam Perspektif Guru SMK - Safrinanda Harahap; Arif Boy Wilson; Muhammad Maulana Syahputra; Ambya Ambya; Mahesi Agni Zaus (Departement of Mathematics Education, 2023)
Education is very functioning for the nation and youth, especially for children in the world of education in achieving goals. The implementation of useful education can be seen from qualified teachers who also teach wholeheartedly in conveying material. There are many factors that lead to success including learning methods where teachers are expected to be even more creative in developing learning methods, therefore there is an evaluation of learning. This research method is a literature study with a qualitative approach. The results obtained are the importance of supervision from supervisors or principals in improving teacher education and success in teaching and achieving goals in the freedom to develop ideas while studying